A Congruent‐Melting Mid‐Infrared Nonlinear Optical Vanadate Exhibiting Strong Second‐Harmonic Generation. (6th September 2021) - Wu, Chao; Jiang, Xingxing; Lin, Lin; Hu, Yilei; Wu, Tianhui; Lin, Zheshuai; Huang, Zhipeng; Humphrey, Mark G.; Zhang, Chi
Abstract: Study of mid‐infrared (mid‐IR) nonlinear optical (NLO) materials is hindered by the competing requirements of optimized second‐harmonic generation (SHG) coefficient dij and laser‐induced damage threshold (LIDT) as well as the harsh synthetic conditions. Herein, we report facile hydrothermal synthesis of a polar NLO vanadate Cs4 V8 O22 (CVO) featuring a quasi‐rigid honeycomb‐layered structure with [VO4 ] and [VO5 ] polyhedra aligned parallel. CVO possesses a wide IR‐transparent window, high LIDT, and congruent‐melting behavior. It has very strong phase‐matchable SHG intensities in metal vanadate family (12.0 × KDP @ 1064 nm and 2.2 × AGS @ 2100 nm). First‐principles calculations suggest that the exceptional SHG responses of CVO largely originate from virtual electronic transitions within [V4 O11 ]∞ layer; the excellent optical transmittance of CVO arises from the special characteristics of vibrational phonons resulting from the layered structure. Abstract : Access to the elusive mid‐infrared by direct second‐harmonic generation (SHG) enabled by a vanadate crystal is reported. Cs4 V8 O22 exhibits a wide transparent range, a strong SHG response, a large laser damage threshold and congruent‐melting behavior. Quantum mechanical calculations demonstrate the key role played by its quasi‐rigid layered structure in the improvement in linear and second‐order nonlinear optical performance.